Ischaemic cardiovascular mortality in patients with non-valvular atrial fibrillation according to CHADS2 score - Kim, Young Dae; Cha, Myoung Jin; Kim, Jinkwon; Lee, Dong Hyun; Lee, Hye Sun; Nam, Chung Mo; Nam, Hyo Suk; Heo, Ji Hoe (Thrombosis and Haemostasis, 2011)
The CHADS2 score predicts the risk of ischaemic stroke in patients with non-valvular atrial fibrillation (NVAF). Most components of the CHADS2 score are also risk factors of atherosclerosis, and clustering of these risk factors is associated with increased risk of cardiovascular disease, including ischaemic heart disease. The aim of this study was to investigate whether the CHADS2 score and CHA2DS2-VASc score are predictive of fatal ischaemic heart disease as well as fatal ischaemic stroke. Among 5,268 stroke patients admitted between August 1994 and December 2008, 770 stroke patients with NVAF were enroled in this study. The relationship between CHADS2 score or CHA2DS2-VASc score and the fatal ischaemic events was examined using a Cox regression model. During the follow-up period of 1156.0 ± 1205.0 days (median 729.5, in-terquartile range 179.0 – 1751.0), 321 patients died (41.7%). The CHADS2 score or CHA2DS2-VASc score was positively correlated with fatal ischaemic heart disease as well as with fatal ischaemic stroke. After adjustment for all potential confounders, the occurrence of fatal ischaemic heart disease was independently associated with CHADS2 score or CHA2DS2-VASc score, and previous history of ischaemic heart disease. The CHADS2 and CHA2DS2-VASc scores provide valuable information for identifying high-risk individuals for fatal ischaemic heart and brain diseases among stroke patients with NVAF.
Keywords: Stroke; ischaemic heart disease; atrial fibrillation; mortality